Normal subdigroups and the isomorphismtheorems for digroups (2016)
ABSTRACT: We discuss the notion of normality of a sub-object in the category of digroups. This allows us to define quotient digroups, and then establish the corresponding analogues of the classical Isomorphism Theorems.